Macromineral requirements for maintenance in male and female Saanen goats: A meta-analytical approach - Vargas, Julián Andrés Castillo [UNESP]; Almeida, Amélia Katiane [UNESP]; Souza, Anaiane Pereira [UNESP]; Fernandes, Márcia Helena Machado da Rocha [UNESP]; Härter, Carla Joice [UNESP]; de Resende, Kléber Tomás [UNESP]; Teixeira, Izabelle Auxiliadora Molina de Almeida [UNESP] (Elsevier, 2020)
The objective of this study was to evaluate the effects of sex on the daily net requirements of calcium (NCam), phosphorus (NPm), potassium (NKm), and magnesium (NMgm) for maintenance in Saanen goats from 5 to 45 kg BW. Two datasets were used: the first dataset was composed of 154 individual records (53 castrated males, 46 females, and 55 intact males) from three studies, and was used to estimate the NCam, NPm, NKm, and NMgm using the comparative slaughter technique (CST). The second dataset was assembled from 160 individual records (67 castrated males, 45 females, and 48 intact males) from four feeding trials, and was used to estimate the NCam, NKm, and NMgm in Saanen goats, using the minimum endogenous losses method (MEL). A meta-analytic approach was applied using a mixed model, in which sex was considered a fixed effect and study a random effect. Using the CST, the results revealed that sex did not affect NCam, NPm, or NKm (21.1, 22.8, and 4.0 mg/kg BW, respectively; P > 0.10), but NMgm of intact males was greater than for castrated males or females (2.6 versus 1.4 mg/kg BW; P = 0.077). On the other hand, sex did not affect the NCam, NKm, or NMgm (38.0, 25.2, and 7.4 mg/kg BW, respectively; P > 0.10), when MEL was used. The findings of this study suggest that Ca, P, and K requirements for maintenance in goats are not influenced by sex. Conversely, Mg requirement for maintenance should be discriminated by sex. Also, that P requirements for maintenance were significantly lower than current feeding system recommendations.
Keywords: Comparative slaughter; Dairy goat; Meta-analysis; Mineral requirement; Sex